Mirmecofauna em área de mineração de carvão no Rio Grande do Sul - Pedron, Leandra (2016)
The aim of this study was to evaluate the biodiversity of ants in coal mining area in the city of Candiota, Rio Grande do Sul. Thus, two methods of sampling were used and, as a result, this work was divided into two chapters. In the first chapter, the survey of the mirmecofauna was carried out monthly with attractive bait in the period from July 2014 to June 2015. It was used the Completely Randomized Design (CRD) with seven treatments, which are: native grassland, non-mined area; native grassland, mined area; plantation of Acacia mearnsii, non-mined area; plantation of Acacia mearnsii, mined area; plantation of Eucalyptus dunnii, non-mined area; plantation of Eucalyptus dunnii, mined area 1; and plantation of Eucalyptus dunnii, mined area 2. Each treatment was composed of 10 baits, in every date of collection. 35,389 specimens belonging to five subfamilies, nine tribes, 15 genera and 40 species were collected. In the area with native grassland, non-mined area, there was the largest number of species and the in the planted area of Acacia mearnsii, mined area, there was the highest level of species richness (Sobs = 25). There was no statistical difference between the mean plenty of treatments, but there was a difference between the means of richness of the treatments. The genera such as Pheidole, Camponotus and Solenopsis were the most abundant in all treatments. It is concluded that nonmined areas and mined areas that passed through the recovery process does not interfere with the total of collected specimens and species richness. In the second chapter, soil mirmecofauna sampling was carried out with use of Berlese Funnel. The survey was performed monthly from July 2014 to June 2015. CRD was used in six treatments: native grassland, non-mined area; native grassfield, mined area; plantation of Acacia mearnsii, non-mined area; plantation of Acacia mearnsii, mined area; plantation of Eucalyptus dunnii, non-mined area; and plantation of Eucalyptus dunnii, mined area. Four soil samples were collected in each treatment, in every date of collection. In the laboratory, the samples were placed in Berlese Funnels, where they remained seven days under incandescent light. 2,105 specimens were collected, divided into four subfamilies, eight tribes, 16 genera and 31 species. The highest abundance and the largest number of collected species was in the area with native grassland, non-mined area (Sobs = 18). There was statistical difference between the means of abundance and species richness among treatments. Thus, it is possible to conclude that the total number of collected and the richness of specimens differ between mined and non-mined areas.